2020
DOI: 10.1007/s12190-020-01442-4
|View full text |Cite
|
Sign up to set email alerts
|

On the global asymptotic stability of a system of difference equations with quadratic terms

Abstract: Zhang Y, Yang X, Evans DJ, Zhu C. On the nonlinear di¤erence equation system x n+1 = A + x n m =yn, y n+1 = A + y n m =xn.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…E. Tasdemir [17] studied the global asymptotic stability of the following system of difference equations with quadratic terms…”
Section: Introductionmentioning
confidence: 99%
“…E. Tasdemir [17] studied the global asymptotic stability of the following system of difference equations with quadratic terms…”
Section: Introductionmentioning
confidence: 99%
“…Finally, they showed that the positive solutions of System (3) are boundedness and persistence, and that the unique positive equilibrium point of System (2) is globally asymptotically stable. Other related difference equations and systems of difference equations can be found in references [10][11][12][13][14][15][16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…In [12], Taşdemir investigated the oscillation, global asymptotic stability and rate of convergence of solutions of following system of second order difference equations with quadratic terms…”
Section: Introductionmentioning
confidence: 99%